The Welfare State: The Challenges of Sustainability - Kuhnle, Stein (Socialinė teorija, empirija, politika ir praktika, 2023)
It is nothing new that ‘the welfare state’ faces serious challenges. Ever since the 1970s, Western welfare states have by many researchers been regarded as being in crisis, but despite many policy adjustments and important variations among Western welfare states, the overall scope of the welfare state, as measured by social expenditure per capita, has by and large increased. At the same time, we can observe a globalization of social policy and the emergence of a more active social role of the state in many parts of the world during recent decades.But new challenges due to a variety of new security issues and new dimensions of uncertainty have appeared, not least following the unanticipated Russian large-scale invasion of and war on Ukraine and concomitant international political developments. Political unease about the future of the welfare state and scope of social policies in different parts of the world has escalated. Welfare political priorities must compete with increased priorities for defense, cyber security, and issues related to energy, climate, food, and the environment.Motivations for state responsibility for citizen welfare and well-being – as well as for the type and scope of responsibility - vary. The fate of the welfare state and social policies is clearly a question of political and normative commitment to what kind of socially active state is desired. The paper addresses the following topics: Why should a state be socially active? What were historical reasons for developing welfare states? What are current motivations for developing and maintaining welfare states? What are the economic, political, and moral dimensions of welfare state sustainability? In addition to possible national political responses to social challenges, it is argued that in a globalized world reinforced international cooperation, coordination and regulation may be necessary to achieve sustainability of (national) welfare states.
Keywords: Welfare states; challenges; sustainability; universal rights; social protection